INTEGRASI ILMU: TANTANGAN KOMPLEKS DALAM MASYARAKAT MODERN - Afriandi, Afriandi; Lilis Surianti; Cahya Dwi Utari Haris; Diah Ayu Dewi; Suci Lestari; Irda; Hasbi (TEKNOS: Jurnal Pendidikan dan Teknologi, 2024)
This research discusses the concept of Science Integration and Types of Science Integration Paradigms. The aim of this journal is to investigate and deepen the concept and practice of science integration, and reveal its benefits in solving complex problems in various fields of knowledge. The method used in preparing this journal is library research, by reviewing several literature regarding the integration of science and its types of paradigms. As a result, we can find out what integration of science is and its benefits for Islamic education. Based on the results of the literature review, this journal explains that the concept of integration of science and religion is divided into two meanings, namely reintegration and integrative. This journal also identifies several types of science integration paradigms, such as the Islamization of Science Paradigm, Islamic Science, Integration-interconnection, and Transdisciplinary Paradigm.